Sobre equações e funções na educação básica, uma análise de erros - Sousa, Jean Carlos Fideles de (2014)
In this work we made a brief study of the affine function, the equation of the first degree and na analysis of the major mistakes made by students in addressing these. Initially we present the field of real numbers, we study the following affine function, which has this set as domain, and show that is graph is a straight line. To calculate the zero affine afunction faced with an equation of the first degree, so in the next section, we briefly present the equation of the first degree. In chapter two we present the results obtained from the survey conducted in a public school, and it pointed out the mistakes made by students in the understanding of these two concepts of equation and function.